2009
DOI: 10.4314/bjpm.v11i1.48823
|View full text |Cite
|
Sign up to set email alerts
|

Quality Of Life Of People Living With Hiv/Aids In Kogi State, Nigeria

Abstract: were observed in social relationships (13.2±2.5) and environment (13.1±1.9) domains. A significant difference in mean QoL scores in the level of independence domain was observed among women (14.4±1.9) compared to men (13.9±1.7; p=0.028). Conclusions: Lower QoL in the environment and social relationships domains may be suggestive of stigma and discrimination, as well as poor living conditions, in the PLWHA physical environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
34
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 11 publications
11
34
3
Order By: Relevance
“…In a study, Fatiregun et al concluded that out of total study population 17.5% were illiterate, 28.6% patients had primary education, 38.9% had secondary education and 15.1% had tertiary education. 14 Majority of the study subjects were 59.25% employed and 40.75% were unemployed. Majority of the subjects 27.9% were skilled worker, (21.6%) were unskilled workers i.e., mainly daily wage earners, 9.7% were semiskilled workers and 34.8% are housewife.…”
Section: Socio Demographic Factorsmentioning
confidence: 99%
“…In a study, Fatiregun et al concluded that out of total study population 17.5% were illiterate, 28.6% patients had primary education, 38.9% had secondary education and 15.1% had tertiary education. 14 Majority of the study subjects were 59.25% employed and 40.75% were unemployed. Majority of the subjects 27.9% were skilled worker, (21.6%) were unskilled workers i.e., mainly daily wage earners, 9.7% were semiskilled workers and 34.8% are housewife.…”
Section: Socio Demographic Factorsmentioning
confidence: 99%
“…For instance, women living with HIV/AIDS have a worse quality of life than men 8,9,10,11,12,13 . However, one study has reported no differences in quality of life with regard to gender 14 and another has shown better quality of life among women 15 . It is important to take into account the various cultural issues involving gender in the different regions where these studies were performed, a fact that may in some way have influenced the results.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, studies have reported better QoL in the spiritual domain with better adherence [7,44]. The reasons for better adherence in subjects with high spiritual and religious scores in this study could be due to better support and teachings from religious institutions and a positive psychological impact of private religious activities such as prayers and scripture reading.…”
Section: Discussionmentioning
confidence: 83%
“…More than half of the subjects were of Pentecostal denomination (224, 60.5%), Roman Catholic (69, 18.7%), and Orthodox (44, 11.9%); other denominations consisted of mainly "white garment" (29,7.8%) and Islam (4, 1.1%).…”
Section: Religious and Spiritual Characteristics Of Subjectsmentioning
confidence: 99%
See 1 more Smart Citation